Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376312
|View full text |Cite
|
Sign up to set email alerts
|

A Change of Perspective: How User Orientation Influences the Perception of Physicalizations

Abstract: Figure 1. The 6 exemplar physicalizations (Phys1-Phys6) and a depiction of the experiment setup. The physicalizations were presented to participants from 4 different orientations according to the vertices of the plane. Participants completed 3 tasks including clustering, filtering and finding the extremum in the abstract 'data'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 25 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…However, we still lack an understanding of how users approach and interact with composite physicalizations and the facets of their distinct qualities. This includes the perception of size for different physical shapes [16], the effect of user orientation on the perception of physical information [29], and the interweaving of the material and social aspects of tangible interaction [12]. In addition, shape-changing physicalizations are currently bound to the limitations of technology for their implementation and often explored and studied in those terms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we still lack an understanding of how users approach and interact with composite physicalizations and the facets of their distinct qualities. This includes the perception of size for different physical shapes [16], the effect of user orientation on the perception of physical information [29], and the interweaving of the material and social aspects of tangible interaction [12]. In addition, shape-changing physicalizations are currently bound to the limitations of technology for their implementation and often explored and studied in those terms.…”
Section: Introductionmentioning
confidence: 99%
“…In response to the highlighted gaps in understanding users and their interaction with physicalizations [12,16,29], our work focuses on interaction with composite bar chart physicalizations, to inform the next generation of interactive dynamic composite physicalizations. We conducted an experiment with six abstract exemplar physicalizations, informed by prior work on the well-known physical 3D bar charts [5,7,9,34], to observe technologically unconstrained direct physical manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the readability of LOOP changed over time as occlusion of the rings occurred. Participants reported on different strategies to read the visualization and observed LOOP from different perspectives, making the physicalization prone to incorrect interpretations as shown by prior work [33]. Future work could investigate how different orientations of the entire system (e.g.…”
Section: Visualization Mappingmentioning
confidence: 91%
“…For instance, Jansen and Hornbaek [16] have shown consistent biases in viewers' perception of physicalizations that use size as a physical variable (reminiscent of similar biases in 2D and 3D onscreen representations). Similarly, Sauvé et al [17] have shown that the orientation and layout of a physicalization can drastically change how viewers interpret it.…”
Section: Physical Visualizationsmentioning
confidence: 93%